2021
DOI: 10.3892/mmr.2021.11946
|View full text |Cite
|
Sign up to set email alerts
|

Functions of circular RNAs in bladder, prostate and renal cell cancer (Review)

Abstract: Circular RNAs (circRNAs) are a class of non-coding RNAs formed by covalently closed loops through back-splicing and exon-skipping. circRNAs have been confirmed to play a vital role in various biological functions, acting as microRNA sponges and reservoirs, as well as combining with RNA-binding proteins during the progression of multiple cancer types. Therefore, the present review evaluated recent research articles in PubMed that were published between November 2017 and September 2020. Key word search strings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 76 publications
(91 reference statements)
2
64
0
Order By: Relevance
“…These findings indicate the potential of circRNAs to be effective biomarkers. Furthermore, as previously reported, circRNAs have a critical role in promoting metastasis in RCC ( Yang et al, 2021 ). CircRNAs can contribute to tumorigenesis in RCC and promote proliferation and differentiation of RCC by regulating tumor-related signaling pathways ( Li et al, 2020a ) and activating transcription factors ( Chen et al, 2020a ).…”
Section: Introductionsupporting
confidence: 63%
“…These findings indicate the potential of circRNAs to be effective biomarkers. Furthermore, as previously reported, circRNAs have a critical role in promoting metastasis in RCC ( Yang et al, 2021 ). CircRNAs can contribute to tumorigenesis in RCC and promote proliferation and differentiation of RCC by regulating tumor-related signaling pathways ( Li et al, 2020a ) and activating transcription factors ( Chen et al, 2020a ).…”
Section: Introductionsupporting
confidence: 63%
“…In recent years, circRNAs have attracted increasing research attention for their diverse impacts on the occurrence and development of RCC. Growing evidence hints at a significant role for the expression alterations of cir-cRNAs in biological characteristics of RCC [18,19]. For instance, circTLK1 functioned as an oncogene to expedite the metastasis and growth in RCC by modulating the miR-495-3p/CBL axis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and epigenetic factors are the main ones [38,39]. Multiple recent studies have confirmed that circRNAs play a substantial role in the initiation and progression of various cancers, such as hepatic and renal carcinoma, and bladder, prostate, esophageal, breast, gastric and lung cancer [40][41][42][43][44][45]. Considerable evidence shows that these circRNAs function in a great number of cancers and play essential roles in their occurrence and development [46].…”
Section: Circrnas In Cancermentioning
confidence: 99%